Optical Films and Optical Stacks

By using a polymer layer with a high glass transition temperature and an optical stack with a low energy storage modulus adhesive in the optical stack, the problem of micro-folding phenomenon at high temperature is solved, and a more stable and layer-resistant resistance is achieved. Optical stacking performance.

CN113892045BActive Publication Date: 2025-02-213M INNOVATIVE PROPERTIES CO
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
CN202080036743.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-23
Filing Date
2020-05-20
Publication Date
2025-02-21
Estimated Expiration
2040-05-20

AI Technical Summary

Technical Problem

Existing optical stacks are prone to micro-folding at high temperatures, resulting in ripples or buckling of the film layer, affecting the performance of the display.

Method used

An optical stack of linear absorption polarizers and reflective polarizers, the reflective polarizers including a plurality of alternating first polymer layers and a second polymer layer, the first polymer layer having more than the second polymer layer. A small average in-plane refractive index and has a glass transition temperature of at least 107°C. Meanwhile, the optical film is bonded to the absorbent polarizer using an adhesive with a low energy storage modulus and a high tan δ.

Benefits of technology

By controlling the shrinkage difference between the optical film and the reflective polarizer, the micro-wrinkle phenomenon is reduced, and the stability and layer resistance of the optical stack are improved. It is suitable for display applications in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113892045B_ABST
    Figure CN113892045B_ABST
Patent Text Reader

Abstract

The present invention discloses an optical film, which includes a plurality of alternating first and second polymer layers, such that the first polymer layer has a smaller average in-plane refractive index than the second polymer layer and the first polymer layer has a glass transition temperature of at least 107°C. The optical film may be a reflective polarizer. The present invention discloses an optical stack, which includes a linear absorptive polarizer and the reflective polarizer, which is disposed on and bonded to the absorptive polarizer. The reflective polarizer has an optical reflectivity of at least 60% for a first polarization state and an optical transmittance of at least 60% for an orthogonal second polarization state. When heated at 105°C for 15 minutes, the difference in shrinkage of the reflective polarizer and the absorptive polarizer along the first polarization state and the second polarization state is greater than about zero and 0.2%, respectively.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] A polarizer stack may include an absorbing polarizer and a reflective polarizer bonded together. Such a polarizer stack may be used in display applications. Summary of the invention

[0002] In some aspects of the present specification, an optical stack is provided, the optical stack including a linear absorptive polarizer and a reflective polarizer disposed on and bonded to the linear absorptive polarizer. For substantially vertically incident light and for at least a first wavelength in the visible wavelength range extending from about 420 nm to about 650 nm: the reflective polarizer has an optical reflectivity of at least 60% for a first polarization state and an optical transmittance of at least 60% for an orthogonal second polarization state, and the linear absorptive polarizer has an optical absorptivity of at least 60% for the first polarization state and an optical transmittance of at least 60% for the second polarization state. When heated at 105° C. for 15 minutes, the difference in shrinkage of the reflective polarizer and the linear absorptive polarizer along the first polarization state and the second polarization state is greater than about zero and 0.2%, respectively. The reflective polarizer includes a plurality of alternating first and second polymer layers, such that for at least the first wavelength, the first polymer layer has an average in-plane refractive index less than that of the second polymer layer. The first polymer layer has a glass transition temperature of at least 107° C.

[0003] In some aspects of the present specification, an integrally formed optical film is provided. The integrally formed optical film includes a plurality of alternating first and second polymer layers, the total number of the plurality of alternating first and second polymer layers being at least 50 and disposed between opposite outermost polymer layers. The thickness of each first and second polymer layer is less than about 400 nm and the thickness of each outermost polymer layer is greater than about 500 nm. The first polymer layer has a glass transition temperature of at least 107° C. and has an average in-plane refractive index smaller than that of the second polymer layer. The minimum average peel strength between the two portions of the integrally formed optical film is greater than about 0.4 N / cm, wherein each of the two portions includes one outermost polymer layer of the outermost polymer layers. In some embodiments, an optical stack includes a linear absorbing polarizer and an integrally formed optical film, the optical film being disposed on the linear absorbing polarizer and bonded to the linear absorbing polarizer. BRIEF DESCRIPTION OF THE DRAWINGS

[0004] Figure 1 is a schematic cross-sectional view of an optical stack;

[0005] Figure 2 is a schematic diagram of the transmission axis of a reflective polarizer and a linear absorbing polarizer;

[0006] Figure 3 is a schematic cross-sectional view of an optical component;

[0007] Figure 4 is a schematic cross-sectional view of an optical film;

[0008] Figure 5 is a schematic diagram of the peel test;

[0009] Figure 6 is a graph showing the layer thickness distribution of a reflective polarizer;

[0010] Figure 7 yes Figure 6 A graph of transmittance versus wavelength of a reflective polarizer;

[0011] Figure 8 is a graph showing layer thickness distribution of another reflective polarizer; and

[0012] Fig. 9 yes Figure 8 A graph of the transmittance versus wavelength of a reflective polarizer. DETAILED DESCRIPTION

[0013] In the following description, reference is made to the accompanying drawings, which form a part of the present invention and in which various embodiments are shown by way of example. The drawings are not necessarily drawn to scale. It should be understood that other embodiments may be conceived and carried out without departing from the scope or essence of the present description. Therefore, the following specific embodiments should not be considered to have a limiting meaning.

[0014] Optical stacks, which include an absorbing polarizer and an optical film and / or a reflective polarizer, can be used in a variety of display applications. For example, the inner polarizer (the polarizer facing away from the viewer) in a liquid crystal display (LCD) can include an optical stack that includes a reflective polarizer facing the backlight and an absorbing polarizer facing the display panel. Polarizer stacks and their use in display applications are generally described, for example, in U.S. Pat. No. 6,025,897 (Weber et al.).

[0015] A problem with using an optical stack with an absorbing polarizer and a conventional reflective polarizer in a display is the phenomenon of microwrinkling, which refers to ripples / buckling in the layers of the film. Such microwrinkling can occur during lamination of the optical stack to a component, or over time. For example, an optical stack can be used in automotive applications (e.g., LCD displays in automobiles), where the optical stack can be exposed to elevated temperatures, which can cause microwrinkling. Microwrinkling is characterized by adjacent surfaces or interfaces of the multilayer film not being parallel to each other. As described in PCT Application Publication No. WO 2017 / 205106 (Stover et al.) and corresponding U.S. Patent Application No. 16 / 301106, for example, microwrinkling can be reduced by increasing the shrinkage of the reflective polarizing film, which avoids the formation of compressive stress in the reflective polarizing film due to the shrinkage of the absorbing polarizer when exposed to elevated temperatures.

[0016] Multilayer optical films (e.g., reflective polarizing films) typically include alternating high refractive index layers and low refractive index layers. According to the present specification, it has been found that micro-wrinkles can be reduced by selecting a polymer with a higher glass transition temperature for the low refractive index layer than the conventional polymer selected for the low refractive index layer. It is traditionally believed that the low refractive index layer should have a relatively low glass transition temperature (e.g., 105°C or less) so that the multilayer film has sufficient delamination resistance or peel strength between adjacent layers. However, it has been found that the use of a low refractive index layer with a higher glass transition temperature can provide acceptable delamination resistance and result in reduced micro-wrinkles. It has also been found that an adhesive for bonding the multilayer optical film to an absorptive polarizer can be selected to reduce micro-wrinkles. For example, it has been found that an adhesive with a low storage modulus and / or a high tan δ can reduce micro-wrinkles. Any combination of selecting the relative shrinkage of a reflective polarizer or optical film and an absorptive polarizer, selecting the glass transition temperature of a low refractive index layer, or selecting an adhesive can be used to reduce micro-wrinkles.

[0017] Figure 1 1 is a schematic cross-sectional view of an optical stack 100 including a linear absorbing polarizer 110 and an optical film and / or reflective polarizer 110 disposed on and bonded to a linear absorbing polarizer 120. In the illustrated embodiment, the optical film and / or reflective polarizer 110 and the linear absorbing polarizer 120 are bonded together with an adhesive 130. In some embodiments, the optical film and / or reflective polarizer 110 is an integrally formed optical film. In some embodiments, the integrally formed optical film is a reflective polarizer whose transmission axis is substantially aligned with the transmission axis of the linear absorbing polarizer.

[0018] Figure 2is a schematic diagram of a transmission axis 112 of a reflective polarizer and a transmission axis 122 of a linear absorptive polarizer. An angle θ between transmission axes 112 and 122 is shown. For example, when the angle is less than about 30 degrees, the transmission axes can be described as being substantially aligned. In some embodiments, angle θ is less than about 30 degrees, or less than about 10 degrees, or less than about 5 degrees, or less than about 3 degrees.

[0019] In some embodiments, the optical stack 100 includes a reflective polarizer 110 and a linear absorptive polarizer 120, which are bonded together using an adhesive 130 having a storage modulus G' at 105°C of less than about 10 kPa and a loss modulus G" at 105°C such that the ratio of the loss modulus G" to the storage modulus G' (tan δ) is at least about 0.4, or at least about 0.5, or at least about 0.6. In some such embodiments or in other embodiments, the adhesive 130 has a storage modulus G' at 105°C of less than about 8 kPa. It has been found that the use of an adhesive having a low (e.g., less than about 10 kPa or less than about 8 kPa) storage modulus and / or a high tan δ (at least about 0.4, or at least about 0.5, or at least about 0.6) reduces microwrinkles of the optical stack. The moduli G' and G" may be determined using, for example, dynamic mechanical analysis (DMA). Unless otherwise indicated, the moduli G' and G" are determined at a frequency of 1 Hz. For example, the modulus may be determined according to the ASTM D4065-12 test standard.

[0020] In some embodiments, when heated at 105° C. for 15 minutes, the reflective polarizer 110 and the linear absorbing polarizer 120 are polarized in orthogonal first and second polarization states (eg, in a direction parallel to the polarization direction of the reflective polarizer 110 and the linear absorbing polarizer 120). Figure 3215 and the second polarization state 219 depicted in the drawings) are greater than about zero and 0.2%, respectively (e.g., greater than -0.01% and 0.18%, respectively, or greater than 0% and 0.2%, respectively, or greater than 0.01% and 0.22%, respectively). For example, the linear absorbing polarizer 120 may have a shrinkage of 0.1% and 0.3% along the transmission axis and the block axis, while the reflective polarizer has a shrinkage of 0.3% and 0.6% along the transmission axis and the block axis, so that the difference in shrinkage of the reflective polarizer and the absorbing polarizer along the transmission axis and the block axis is 0.2% and 0.3%, respectively. In some embodiments, the difference in shrinkage of the reflective polarizer 110 and the linear absorbing polarizer 120 along the second polarization state is greater than about 0.25% or greater than about 0.3%. In some embodiments, the difference in shrinkage of the reflective polarizer 110 and the linear absorbing polarizer 120 along the first polarization state is greater than about 0.05%, or greater than about 0.1%, or greater than about 0.15%. The difference in shrinkage along each polarization state may be less than 5%, or less than 3%, or less than 1%. It has been found that, for example, having the difference in shrinkage within these ranges results in reduced microwrinkling of the optical stack during lamination of the optical stack to other components or during aging at elevated temperatures. As further described elsewhere herein, the difference in shrinkage can be controlled by controlling the shrinkage of the optical film and / or the reflective polarizer 110.

[0021] Figure 3 1 is a schematic cross-sectional view of an optical member 250 that may correspond, for example, to the optical film 110 or the linear absorbing polarizer 120. The optical member 250 may be one or more of a linear absorbing polarizer, an optical film, a reflective polarizer, or a plurality of alternating first and second polymer layers. A substantially vertical (e.g., within 30 degrees, or within 20 degrees, or within 10 degrees, or within 5 degrees of vertical) incident light 213 having a first wavelength λ1 and having a first polarization state 215 is schematically shown. Portion 233 of the incident light 213 is reflected (optical reflectivity times incident energy), portion 253 of the incident light 213 (schematically shown by the dashed line without arrows) is absorbed (optical absorbance times incident energy), and portion 243 of the incident light 213 is transmitted (optical transmittance times incident energy). A substantially vertical incident light 217 having a first wavelength λ1 and having a second polarization state 219 orthogonal to the first polarization state 215 is schematically shown. Portion 237 of incident light 217 is reflected (optical reflectivity times incident energy), portion 257 of incident light 217 is absorbed (optical absorptivity times incident energy), and portion 247 of incident light 217 is transmitted (optical transmittance times incident energy).

[0022] In some embodiments, for substantially normal incident light and for at least a first wavelength in the visible wavelength range extending from about 420 nm to about 650 nm: the reflective polarizer has an optical reflectivity of at least 60% for a first polarization state 215 and an optical transmittance of at least 60% for an orthogonal second polarization state 219, and the linear absorptive polarizer has an optical absorptivity of at least 60% for the first polarization state 215 and an optical transmittance of at least 60% for the second polarization state 219. In some embodiments, the reflective polarizer includes a plurality of alternating first and second polymer layers. In some embodiments, for substantially normal incident light and for at least a first wavelength, the plurality of alternating first and second polymer layers have an optical reflectivity of greater than about 80% for the first polarization state 215, an optical transmittance of greater than about 85% for the second polarization state 219, and an optical transmittance of less than about 0.1% for the first polarization state 215. In some embodiments, the linear absorbing polarizer has an optical absorptivity of at least 70% for the first polarization state 215 and an optical transmittance of at least 70% for the second polarization state 219 .

[0023] Multilayer optical films that provide desired transmission and / or reflection properties at least in part by an arrangement of microlayers having different refractive indices are known. For example, such optical films have been demonstrated by extruding alternating polymer layers, casting the layers onto a chill roll via a film die, and then stretching the cast web. See, for example, U.S. Pat. Nos. 3,610,729 (Rogers), 4,446,305 (Rogers et al.), 4,540,623 (Im et al.), 5,448,404 (Schrenk et al.), 5,882,774 (Jonza et al.), 6,157,490 (Wheatley et al.), 6,783,349 (Neavin et al.), and 9,279,921 (Kivel et al.) and International Application Publication No. 2018 / 163009 (Haag et al.). In these polymeric multilayer optical films, the polymer material may be primarily or exclusively used to constitute each layer. Such films are suitable for high-volume manufacturing processes and can be produced in large sheets and rolls.

[0024] The shrinkage of the multilayer optical film can be controlled by controlling the stress during the cooling of the film after the film is stretched. It has been generally found that higher stress during this cooling period leads to a larger shrinkage. In some embodiments, heat setting is applied after the film is stretched. Heat setting can be carried out in the last zone of the tenter oven for orienting the film, as described in U.S. Patent 6,827,886 (Neavin et al.). Typically, such heat setting treatment is used to reduce the shrinkage of the film or minimize the shrinkage of the film when heat is subsequently applied to the film. When it is desired to minimize the subsequent shrinkage of the film, the heat setting temperature can be set to the highest temperature that does not cause the film to break in the tenter, and the film can be relaxed in the transverse direction near the heat setting zone, which reduces the tension of the film. Higher shrinkage can be achieved by reducing the heat setting temperature, by shortening the duration of the heat setting treatment at a given heat setting temperature, and / or by eliminating the heat setting step, especially in the longitudinal direction (usually along the light transmission axis when the optical film is a reflective polarizer). Higher shrinkage can be achieved, especially in the transverse direction (usually along the light-blocking axis when the optical film is a reflective polarizer), thereby reducing the relaxation of the film in the light-blocking direction. This can be done, for example, by adjusting the spacing between the tenter rails after heat setting. Reducing this spacing is often referred to as in-beam. The effects of heat setting temperature and in-beam on film shrinkage are described, for example, in U.S. Patent Application No. 6,797,396 (Liu et al.). Therefore, by controlling the heat setting and in-beam conditions, when the optical film is heated at 105°C for 15 minutes, the desired shrinkage in the transverse and longitudinal directions can be achieved. The shrinkage of the optical device can be measured according to, for example, the ASTM D2732-14 test standard "Standard Test Method for Unrestrained Linear Thermal Shrinkage ofPlastic Film and Sheeting".

[0025] Figure 4is a schematic cross-sectional view of an optical film 310, which may be a reflective polarizer, including a plurality of alternating first polymer layers 361 and second polymer layers 362, which are disposed between opposite outermost layers 366 and 368 of the optical film 310. The optical film 310 may be an integrally formed optical film, and the outermost layers 366 and 368 may be polymer layers. In some embodiments, the first polymer layer 361 has a smaller average in-plane refractive index (an average of the refractive indices along two orthogonal in-plane directions, such as along orthogonal first polarization states and second polarization states) than the second polymer layer 362. For example, the second polymer layer 362 may be an oriented layer having a larger refractive index along a first in-plane direction and a smaller refractive index along a second in-plane direction, and the first polymer layer 361 may have substantially the same refractive index along each of the first in-plane direction and the second in-plane direction, which is substantially equal to the refractive index of the second polymer layer along the second in-plane direction. For example, in Figure 3 The refractive index is specified at a first wavelength λ1 of . If no wavelength is specified otherwise, the refractive index is understood to be the refractive index determined at a wavelength of 532 nm. The in-plane direction refers to the direction in the plane of the film when the film is laid flat, or if the film is bent, it refers to the direction in the plane tangential to the film.

[0026] In some embodiments, at least the second polymer layer 362 is substantially uniaxially oriented. For example, in some embodiments, the optical film 310 is a reflective polarizer that is a substantially uniaxially stretched film and has a degree of uniaxiality U of at least 0.7, or at least 0.8, or at least 0.85, where U = (1 / MDDR - 1) / (TDDR 1 / 2 –1), where MDDR is defined as the machine direction stretch ratio and TDDR is defined as the transverse direction stretch ratio. Such substantially uniaxially oriented multilayer optical films are described, for example, in US Pat. No. 2010 / 0254002 (Merrill et al.).

[0027] In some embodiments, the thickness of each of the first polymer layer 361 and the second polymer layer 362 is less than about 500 nm, or less than about 400 nm, or less than about 300 nm, or less than about 250 nm. The thickness of the first polymer layer 361 and the second polymer layer 362 can be selected to provide a desired reflectivity for light of a given wavelength (e.g., the total optical thickness of a pair of adjacent layers can be selected to be half of a given wavelength). The thickness of the first polymer layer 361 and the second polymer layer 362 can vary over the thickness of the optical film to provide a desired reflectivity over a predetermined wavelength range (e.g., extending from about 450 nm to about 650 nm, or from about 420 nm to about 650 nm, or from about 400 nm to about 700 nm).

[0028] The total amount of the first polymer layer 361 and the second polymer layer 362 may be substantially greater than Figure 4 In some embodiments, the total number of the plurality of alternating first polymer layers 361 and second polymer layers 362 is at least 50 (e.g., 100 to 500 layers in total) and is disposed between opposite outermost polymer layers 366 and 368, wherein the thickness of each first polymer layer 361 and second polymer layer 362 is less than about 400nm, and the thickness of each outermost polymer layer 366 and 368 is greater than about 500nm. In some embodiments, the plurality of alternating first polymer layers 361 and second polymer layers 361 of the optical film 310 are disposed between opposite outermost layers 366 and 368 of the optical film 310, wherein each outermost layer 366, 368 has a thickness of about 0.5 microns to about 5 microns. In some embodiments, the thickness of each outermost polymer layer 366 and 368 is less than about 2 microns or less than about 1.5 microns or less than 1 micron. It has been found that the use of an outermost layer having such a thickness can improve the anti-delamination property of the optical film.

[0029] In some embodiments, for substantially normally incident light within a predetermined wavelength range, the optical film 300 or the plurality of alternating first and second polymer layers 361, 362 has an average optical reflectivity greater than about 80% for a first polarization state, an average optical transmittance greater than about 85% for an orthogonal second polarization state, and an average optical transmittance less than about 0.2% or less than about 0.1% for the first polarization state. Optical films having such transmittance and reflectivity are described, for example, in International Application Publication No. WO 2018 / 163009 (Haag et al.).

[0030] The optical film or reflective polarizer of the present specification can be formed in one piece. As used herein, a first element "formed as one piece" with a second element means that the first element and the second element are manufactured together, rather than being manufactured separately and then combined. Formed as one piece includes manufacturing a first element, followed by manufacturing a second element on the first element. An optical film comprising a plurality of layers is formed in one piece, provided that the layers are manufactured together (e.g., combined into a molten stream and then cast onto a cooling roller to form a cast film, and then oriented to the cast film), rather than being manufactured separately and then combined. An optical film or reflective polarizer formed in one piece may include one or more groups of alternating polymer layers, wherein the thickness of each polymer layer in the alternating polymer layers in each group is less than about 400nm. A layer thicker than about 500nm may separate adjacent groups and / or a layer thicker than about 500nm may be disposed at the outermost surface of one or more groups. Such a layer may be a protective boundary layer (PBL), which is included to prevent the flow profile in the coextruded web of the alternating polymer layers from producing optical defects in the alternating polymer layers.

[0031] In some embodiments, the optical film includes two groups of alternating polymer layers and a plurality (e.g., at least 3 or 3 to 20) of thinner (e.g., less than 400 nm thick or less than 300 nm thick) PBLs disposed between the two groups. This has been found to improve delamination resistance between adjacent groups, as further described in co-owned provisional patent application No. 62 / 852,112, filed May 23, 2019, and entitled "MULTILAYER OPTICAL FILM".

[0032] In some embodiments, the first polymer layer 361 has a glass transition temperature of at least 107°C, or at least 109°C, or at least 112°C, or at least 115°C. In some embodiments, the glass transition temperature of the first polymer layer 361 is no more than 125°C, or no more than 120°C. It has been found that the use of a first polymer layer 361 having a glass transition temperature within any of these ranges results in an optical film 310 having acceptable resistance to delamination and resulting in reduced microwrinkling. In some embodiments, the outermost layers 366 and 368 have a glass transition temperature within any of these ranges. In some embodiments, the outermost layers 366 and 368 are formed of the same material as the first polymer layer 361.

[0033] The glass transition temperature can be determined by, for example, differential scanning calorimetry (DSC). For example, ASTM D3418-15 test standard or ASTM E1356-08 (2014) test standard can be used to determine the glass transition temperature by DSC. Alternatively, the glass transition temperature can be determined by dynamic mechanical analysis (DMA). For example, ASTM E1640-18 test standard can be used to determine the glass transition temperature by DMA. The polymer with the desired glass transition temperature can be formed by blending different polymers with different glass transition temperatures at a ratio that results in the desired glass transition temperature and / or by including different segments in the copolymer at a ratio that results in the desired glass transition temperature. For example, a blend of polycarbonate and copolyester can result in a glass transition temperature within a desired range. In some embodiments, the low refractive index layer (e.g., first polymer layer 361) is formed from a blend of polycarbonate, PETG (copolyester of polyethylene terephthalate (PET) with cyclohexanedimethanol used as a glycol modifier; available from Eastman Chemicals, Knoxville, TN), and PCTG (copolyester of PET with cyclohexanedimethanol used as a glycol modifier, with twice the amount of cyclohexanedimethanol compared to PETG; available from Eastman Chemicals, Knoxville, TN). The ratio of the polycarbonate used can be selected to provide a desired glass transition temperature. In some embodiments, the high refractive index layer (e.g., second polymer layer 362) is formed from polyethylene naphthalate (PEN) or a PEN / polyethylene terephthalate (PET) copolymer. Alternatively, other polymer materials known to be useful in polymeric multilayer optical films can be used.

[0034] The delamination resistance can be characterized by the peeling force between the parts of the optical film. The delamination resistance can be expressed, for example, in grams / inch (understood as grams-force / inch) or N / cm. For example, in some embodiments, the minimum average peel strength between two parts of the integrally formed optical film 310 is greater than about 0.4N / cm (e.g., greater than 0.36N / cm or greater than 0.38N / cm) or greater than about 0.6N / cm or greater than about 0.8N / cm, wherein each of the two parts includes one of the outermost polymer layers 366, 368. In some embodiments, the minimum average peel strength is determined using a substantially 90-degree peel test at a peel speed of about 1.5m / min, wherein the minimum average peel strength is the minimum value of the peel strength averaged over an average time of about 5 seconds.

[0035] Figure 5Schematically illustrated is a peel test applied to an integrally formed optical film 410, which may correspond to, for example, optical film 310. Optical film 410 may be cut into standard sizes for testing (e.g., 1 inch (2.54 cm) wide x 12 inch (30 cm) strips). Double-sided tape 458 (e.g., 3M 665 Double-Sided Tape available from 3M Company, St. Paul, MN) is attached to a plate 455 (e.g., a metal plate), and film 410 is attached to double-sided tape 448. The film 410 is scored (e.g., using a razor blade) near the edge of the film along score line 444, which forms an angle α with the major surface of the plate 455 in the range of, for example, 20 to 60 degrees or 30 to 45 degrees. The tape 459 is applied to the film 410 so that the tape 459 covers at least the scored portion of the film 410 and so that the free end 479 of the tape 459 can be used for the peel test. For example, the tape 459 can be an approximately 1.5 inch (4 cm) strip of 3M396 tape available from 3M Company of St. Paul, Minnesota. The free end 479 used for gripping during the peel test can be folded over on itself to form a non-stick sheet (e.g., approximately 1 / 2 inch (1.3 cm) sheet). A substantially 90 degree peel test is then performed by peeling from the free end 479. For example, the pulling direction (given by Figure 5 The angle β between the applied force F in (shown schematically) and the direction parallel to the top surface of the plate 455 may be about 90 degrees. The peel test is performed at a peel speed (speed of the free end 479 along the pulling direction) in the range of about 1.2m / min to about 1.8m / min (e.g., about 1.5m / min). The peel test can be performed using, for example, an IMASS SP-2000 peel tester (IMASS Inc., Accord, MA, USA). The peel strength is averaged over an average time of about 4 to about 6 seconds (e.g., about 5 seconds). The average peel strength can be determined for each sample in a plurality of samples (e.g., five film samples) for a single average time, or for a single (e.g., longer) sample for multiple intervals of the average time. The minimum value among these average peel strengths is referred to as the minimum average peel strength.

[0036] The peel strength is between the two portions 434 and 435 of the optical film 410, wherein each of the two portions 434, 435 includes an outermost polymer layer (e.g., Figure 4The optical film 410 may be delaminated at an interface between one of the outermost layers and one of the alternating first and second layers (e.g., first layer 361 and second layer 362) of the optical film 410. For example, during a peel test, the optical film 410 may be delaminated at an interface between one of the outermost layers and one of the alternating first and second layers (e.g., first layer 361 and second layer 362), such that one of the two portions 434, 435 includes the delaminated outermost layer and the other of the two portions 434, 435 includes the remainder of the optical film 410. As another example, the optical film 410 may be delaminated at an interface between two inner layers, such that each portion 434 and 435 includes the outermost layer and at least one of the alternating first and second layers. As yet another example, delamination may start at an interface between the outermost layer and one of the alternating first and second layers and then propagate into the inner layers of the optical film 410, such that each portion 434 and 435 includes a portion of the inner layer.

[0037] Example

[0038] Peel strength test method

[0039] Film samples were prepared and cut into 1 inch (2.54 cm) by 12 inch (30 cm) strips. Double-sided tape (3M665 double-sided tape purchased from 3M Company, St. Paul, MN) was attached to the metal plate, and the sample strip was attached to the double-sided tape. Excess film was cut from one end of the plate so that the film was flush with the edge of the plate, while the other edges were scored by cutting at an acute angle using a razor blade. One end of an approximately 1.5 inch (4 cm) strip of tape (3M 396 tape purchased from 3M Company, St. Paul, MN) was folded over itself to form a 1 / 2 inch (1.3 cm) non-stick sheet. The other end of the tape was applied to the scored edge of the film sample. Then, a 90 degree peel test was performed using an IMASS SP-2000 peel tester (Emerson, Inc., Accord, Massachusetts, USA) using a 5 second average time and a peel speed of 60 in / min (1.5 m / min). Five strips were tested for each film sample. For the results given in the examples, the minimum value is reported to compare the weakest or lowest force required to delaminate the layers from each other.

[0040] Shrinkage test method

[0041] Shrinkage was determined generally as described in the ASTM D2732-14 test standard, except that an oven was used instead of a constant temperature liquid bath. Prior to testing, the specimens were conditioned in a desiccant chamber (<20% RH) for greater than 24 hours. The specimens were tested at 105° C. (oven set point) for 15 minutes.

[0042] Comparative Example C1

[0043] A birefringent reflective polarizer optical film was prepared as follows. Two multilayer optical packets were coextruded, each of which included 325 alternating layers of polyethylene naphthalate (PEN) and a low refractive index isotropic layer composed of a blend of polycarbonate and copolyester (PC:coPET) such that the refractive index was about 1.57 and remained substantially isotropic when uniaxially oriented, wherein the PC:coPET weight ratio was approximately 41 wt % PC and 59 wt % coPET, and the Tg was 105.8 degrees Celsius. This isotropic material was selected so that after stretching, its refractive index in both non-stretched directions remained substantially matched to the refractive index of the birefringent material in the non-stretched direction, while in the stretched direction, the refractive index between the birefringent layer and the non-birefringent layer was substantially mismatched. The PEN and PC / coPET polymers were fed from separate extruders to a multilayer coextrusion feedblock where they were assembled into packets of 325 alternating optical layers, plus thicker PC / coPET protective boundary layers on the outside of the stacked optical packets, and between packets, 9 alternating inner protective boundary layers of some optical thickness but not uniform, for a total of 661 layers. The multilayer melt was then cast through a film die onto a chill roll where it was quenched in a conventional manner for polyester films. The cast web was then stretched in a parabolic tenter frame at a temperature of 320° F. in the transverse direction at a ratio of approximately 6:1 as described in U.S. Pat. No. 6,916,440 (Jackson et al.).

[0044] The layer thickness distribution of the optical film of Comparative Example 1 is shown in Figure 6 The transmittance and block transmittance at normal incidence angles are determined and shown in Figure 7 The average transmittances from 450 nm to 650 nm were 0.011% and 86.7% for block polarization and transmit polarization, respectively. The film of Comparative Example 1 had a resulting total thickness of about 58.9 μm as measured by a capacitance gauge. The shrinkage at 105° C. for 15 minutes was about 1.01% in the machine direction (MD) and about 0.15% in the transverse direction (TD). The minimum average peel force was 256.7 g / in.

[0045] A Sanritz 5518 absorbing polarizer including an adhesive layer was laminated to the optical film using the adhesive on the Sanritz polarizer to provide an optical stack.

[0046] Example 1

[0047] A birefringent reflective polarizer optical film was prepared as follows. Two multilayer optical packets were coextruded, each of which had 325 alternating layers of 90 / 10 coPEN (a polymer composed of 90% polyethylene naphthalate (PEN) and 10% polyethylene terephthalate (PET)) and a low refractive index isotropic layer made from a blend of polycarbonate and copolyester (PC:coPET) to have a refractive index of about 1.57 and remain generally isotropic when uniaxially oriented, wherein the PC:coPET weight ratio is approximately 61 wt % PC and 39 wt % coPET, and a Tg of 116.4 degrees Celsius. This isotropic material is selected so that after stretching, its refractive index in both non-stretched directions remains substantially matched to the refractive index of the birefringent material in the non-stretched direction, while in the stretched direction, the refractive index between the birefringent layer and the non-birefringent layer is substantially mismatched. The PEN and PC / coPET polymers were fed from separate extruders to a multilayer coextrusion feedblock where they were assembled into packets of 325 alternating optical layers, plus thicker PC / coPET protective boundary layers on the outside of the stacked optical packets, and between packets, 9 alternating inner protective boundary layers of some optical thickness but not uniform, for a total of 661 layers. The multilayer melt was then cast through a film die onto a chill roll where it was quenched in a conventional manner for polyester films. The cast web was then stretched in a parabolic tenter frame at a temperature of 300° F. in the transverse direction at a ratio of approximately 6:1 as described in U.S. Pat. No. 6,916,440 (Jackson et al.).

[0048] The layer thickness distribution of the optical film of Example 1 is shown in Figure 8 The transmittance and block transmittance at normal incidence angles are determined and shown in Fig. 9 The average transmittance from 450nm to 650nm was 0.021% and 89.2% for block polarization and pass polarization, respectively. The film of Example 1 had a resulting total thickness of about 58.7 as measured by a capacitance gauge. The shrinkage at 105°C for 15 minutes was 0.31% and 0.57% for MD and TD, respectively. The minimum average peel force was 226.9 g / in.

[0049] A Sanritz 5518 absorbing polarizer (available from Sanritz Co., Ltd., Japan) including an adhesive layer was laminated to the optical film using an adhesive on the Sanritz polarizer to provide an optical stack. The shrinkage of the Sanritz polarizer at 105° C. for 15 minutes along the pass axis and block axis was 0.10% and 0.30%, respectively.

[0050] Embodiment 2-8

[0051] Examples 2-8 were prepared in a similar manner to Example 1, except for the changes shown in Table 1. The glass transition temperature (Tg) of the low refractive index optical (LIO) layer was calculated from the glass transition temperatures of the PC and coPET used in the blend. The PC and CoPET loadings, calculated Tg, light-transmitting state shrinkage and light-blocking state shrinkage at 105°C for 15 minutes, the difference Δ between the light-transmitting state shrinkage and light-blocking state shrinkage of the sample and Sanritz polarizer at 105°C for 15 minutes, and the minimum average peel force are reported in Table 1.

[0052] Table 1

[0053]

[0054] Micro-wrinkle test

[0055] 3M 8171 adhesive (available from 3M Company, St. Paul, MN) was laminated to the opposite side of the optical stack of Comparative Example Cl and Examples 1-8 and then laminated to a glass slide.

[0056] Two samples from each stack of Comparative Example C1 and Examples 1-3 were placed in an oven set at 105° C. for 225 hours and in a thermal cycle oven for 20 cycles from 30 minutes at 105° C. to 30 minutes at −40° C. After each oven condition, Comparative Example 1 had microwrinkles, while Examples 1-3 had no microwrinkles.

[0057] Two samples from each stack of Comparative Example C1 and Examples 4-8 were placed in an oven set at 105°C for 24 hours. After 24 hours, they were removed from the oven, allowed to cool to room temperature, and inspected for microwrinkles. Comparative Example 1 had microwrinkles, while Examples 4-8 had no microwrinkles.

[0058] To test the effect of the adhesive between the reflective polarizer and the absorptive polarizer, various adhesives were used between the reflective polarizer of Comparative Example C1 and the Sanritz 5518 absorptive polarizer. The adhesive on the Sanritz polarizer was used to laminate the optical stack to a glass slide. The samples were placed in an autoclave at 50°C and 0.5MPa for 20 minutes to ensure good bonding. The bonded samples were placed in an oven set at 105°C for 24 hours. The samples were then removed from the oven, allowed to cool to room temperature, and inspected for microwrinkles. The results are recorded in the table below. The adhesives were obtained from 3M Company (St. Paul, Minnesota). Modulus was determined using DMA at 105°C.

[0059]

[0060] Terms such as "about" will be understood by those of ordinary skill in the art in the context of use and description in this specification. If the use of "about" as applied to the amount of the expression of characteristic size, quantity and physical property in the context of use and description in this specification is unclear to those of ordinary skill in the art, "about" will be understood to mean within 10% of the specified value. If the use of "about" as applied to the difference of the amount of the expression of characteristic size, quantity and physical property in the context of use and description in this specification is unclear to those of ordinary skill in the art, "about" applied to the difference will be understood to mean within 10% of the amount with the smaller value. For example, if "about zero" as applied to the difference between the amount of 0.275 and the amount of 0.3 is otherwise unclear to those of ordinary skill in the context of use and description in this specification, the difference between the difference and zero is less than 10% of 0.275, and the difference is about zero. A quantity given as about a specified value can be exactly the specified value. For example, if it is not clear to a person of ordinary skill in the art in the context of use and description in this specification, an amount having a value of about 1 means that the amount has a value between 0.9 and 1.1, and the value may be 1.

[0061] All references, patents, and patent applications cited above are hereby incorporated by reference in their entirety in a consistent manner. In the event of inconsistencies or conflicts between an incorporated reference portion and the present application, the information in the foregoing description shall prevail.

[0062] Unless otherwise indicated, the description of the elements in the drawings should be understood to apply equally to the corresponding elements in the other drawings. Although specific embodiments have been illustrated and described herein, it will be appreciated by those of ordinary skill in the art that the specific embodiments shown and described may be replaced with a variety of alternative and / or equivalent implementations without departing from the scope of the present disclosure. The present application is intended to cover any modification or variation of the specific embodiments discussed herein. Therefore, the present disclosure is intended to be limited only by the claims and their equivalents.

Claims

1. An optical stack, comprising: Linear absorbing polarizers; and a reflective polarizer disposed on and bonded to the linear absorptive polarizer, for substantially normally incident light and for at least a first wavelength in the visible wavelength range extending from 420 nm to 650 nm: The reflective polarizer has an optical reflectivity of at least 60% for a first polarization state and an optical transmittance of at least 60% for an orthogonal second polarization state; and The linear absorbing polarizer has an optical absorptivity of at least 60% for the first polarization state and an optical transmittance of at least 60% for the second polarization state; wherein, when heated at 105° C. for 15 minutes, the difference in shrinkage between the reflective polarizer and the linear absorptive polarizer along the first polarization state is greater than zero and less than 1%, and the difference in shrinkage between the reflective polarizer and the linear absorptive polarizer along the second polarization state is greater than 0.2% and less than 1%; and The reflective polarizer comprises a plurality of alternating first and second polymer layers such that, for at least the first wavelength, the first polymer layers have a smaller average in-plane refractive index than the second polymer layers, and the first polymer layers have a glass transition temperature of at least 107°C.

2. The optical stack of claim 1, wherein the first polymer layer has a glass transition temperature of at least 109°C.

3. The optical stack of claim 1, wherein the first polymer layer has a glass transition temperature of at least 115°C. 4 . The optical stack of claim 1 , wherein each of the first polymer layer and the second polymer layer has a thickness less than 500 nm.

5. The optical stack of claim 4, wherein the plurality of alternating first and second polymer layers of the reflective polarizer are disposed between opposing outermost layers of the reflective polarizer, each outermost layer having a thickness of 0.5 microns to 5 microns.

6. The optical stack of claim 1, wherein at least the second polymer layer is substantially uniaxially oriented.

7. An optical stack according to claim 1, wherein for substantially normal incident light and for at least the first wavelength, the plurality of alternating first polymer layers and second polymer layers have an optical reflectivity greater than 80% for the first polarization state, an optical transmittance greater than 85% for the second polarization state, and an optical transmittance less than 0.1% for the first polarization state.

8. An optical stack according to any one of claims 1 to 7, wherein the reflective polarizer and the linear absorptive polarizer are bonded together using an adhesive, the adhesive having a storage modulus G′ at 105°C of less than 10 kPa and having a loss modulus G″ at 105°C such that the ratio of the loss modulus G″ to the storage modulus G′ is at least 0.

5.

9. An optical stack according to claim 1, wherein the plurality of alternating first polymer layers and second polymer layers of the reflective polarizer are arranged between opposite outermost polymer layers of the reflective polarizer, wherein the reflective polarizer is an integrally formed optical film, and the minimum average peel strength between two parts of the integrally formed optical film is greater than 0.4 N / cm, and each of the two parts includes one outermost polymer layer of the outermost polymer layers.

10. The optical stack of claim 9, wherein the minimum average peel strength is greater than 0.6 N / cm or greater than 0.8 N / cm.

11. The optical stack of claim 9, wherein each outermost polymer layer has a thickness of less than 2 microns.

Citation Information

Patent Citations

  • Processes and apparatus for making transversely drawn films with substantially uniaxial character

    US20100254002A1

  • Polarizer stack

    US20190196076A1

  • Multilayered light polarizer

    US3610729A

  • Optical device including birefringent polymer

    US4446305A

  • Coextruded multi-layered articles

    US4540623A